Functional Characterization of Two Novel Intron 4 SERPING1 Gene Splice Site Pathogenic Variants in Families with Hereditary Angioedema - Olga Shchagina; Elena Gracheva; Alyona Chukhrova; Elena Bliznets; Igor Bychkov; Sergey Kutsev; Aleksander Polyakov (Biomedicines, 2023)
Variants that affect splice sites comprise 14.3% of all pathogenic variants in the SERPING1 gene; more than half of them are located outside the canonical sites. To make a clinical decision concerning patients with such variants, it is essential to know the exact way in which the effect of the variant would be realized. The optimal approach to determine the consequences is considered to be mRNA analysis. In the current study, we present the results of functional analysis of two previously non-described variants in the SERPING1 gene (NM_000062.3) affecting intron 4: c.686-1G>A and c.685+4dup, which were detected in members of two Russian families with autosomal dominant inheritance of angioedema type 1. Analysis of the patients’ mRNA (extracted from whole blood) showed that the SERPING1(NM_000062.3):c.685+4dup variant leads to the loss of the donor splice site and the activation of the cryptic site in exon 4: r.710_745del (p.Gly217_Pro228del), while the SERPING1(NM_000062.3):c.686-1G>A variant leads to the skipping of exon 5: r.746_949del (p.Asp229_Ser296del).